Mompreneur and Creative Economy: Contribution to Local Economic Growth (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The role of mompreneurs in the creative economy is increasingly significant in supporting local economic growth. This article explores the relationship between mompreneurship and the creative economy through the Systematic Literature Review (SLR) approach. This study shows that mompreneurs, with innovation and adaptive skills, can create job opportunities, strengthen the family economy, and have a positive impact on local communities. However, challenges such as limited access to capital and social pressures remain major obstacles. This article provides strategic recommendations to support mompreneurs in Indonesia by utilizing digital technology, strengthening the business ecosystem, and improving financial literacy. Thus, mompreneurs can be agents of change in the creative economy that contribute to sustainable economic development.